SARC‐F: a symptom score to predict persons with sarcopenia at risk for poor functional outcomes. Issue 1 (7th July 2015) - Malmstrom, Theodore K.; Miller, Douglas K.; Simonsick, Eleanor M.; Ferrucci, Luigi; Morley, John E.
Abstract : Background: A brief, inexpensive screening test for sarcopenia would be helpful for clinicians and their patients. To screen for persons with sarcopenia, we developed a simple five‐item questionnaire (SARC‐F) based on cardinal features or consequences of sarcopenia. Methods: We investigated the utility of SARC‐F in the African American Health (AAH) study, Baltimore Longitudinal Study of Aging (BLSA), and National Health and Nutrition Examination Survey (NHANES). Internal consistency reliability for SARC‐F was determined using Cronbach's alpha. We evaluated SARC‐F factorial validity using principal components analysis and criterion validity by examining its association with exam‐based indicators of sarcopenia. Construct validity was examined using cross‐sectional and longitudinal differences among those with high (≥4) vs. low (<4) SARC‐F scores for mortality and health outcomes. Results: SARC‐F exhibited good internal consistency reliability and factorial, criterion, and construct validity. AAH participants with SARC‐F scores ≥ 4 had more Instrumental Activity of Daily Living (IADL) deficits, slower chair stand times, lower grip strength, lower short physical performance battery scores, and a higher likelihood of recent hospitalization and of having a gait speed of <0.8 m/s. SARC‐F scores ≥ 4 in AAH also were associated with 6 year IADL deficits, slower chair stand times, lower short physical performance battery scores, having a gait speed of <0.8 m/s, being hospitalized recently, and mortality. SARC‐F scores ≥ 4 in the BLSA cohort were associated with having more IADL deficits and lower grip strength (both hands) in cross‐sectional comparisons and with IADL deficits, lower grip strength (both hands), and mortality at follow‐up. NHANES participants with SARC‐F scores ≥ 4 had slower 20 ft walk times, had lower peak force knee extensor strength, and were more likely to have been hospitalized recently in cross‐sectional analyses. Conclusions: The SARC‐F proved internally consistent and valid for detecting persons at risk for adverse outcomes from sarcopenia in AAH, BLSA, and NHANES.